Evaluation of an enhanced multicast data flow technique in network mobility - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Abdullah, Azween; Mohd. Ramli, Huda Adibah; Islam, Shayla (Science & Engineering Research Support Soc, 2016)
Mobile IPTV applications are becoming very popular worldwide. According to CISCO research, mobile Internet video usage is increasing rapidly each year and soon reaching zettabyte threshold in 2019. With the increase number of traffic, it is a great effort for internet service provider to provide acceptable network performance. The objective of this paper is to mathematically evaluate a new proposed mobile multicast technique to support high performance mobile IP traffic. The new technique enhanced multicast services in Network Mobility Management which is Proxy Mobile IPv6 (PMIPv6). The evaluation is done using mathematical equations that are derived from signaling call flow of the multicast process in the proposed technique. Results are analyzed and compared with the current base solution technique. Using mathematical analysis this paper validates and highlights the strengths of the proposed technique compared to the existing technique.